Activated Platelets‐Targeting Micelles with Controlled Drug Release for Effective Treatment of Primary and Metastatic Triple Negative Breast Cancer. (9th January 2019) - Zhang, Yujie; Zhu, Xi; Chen, Xinli; Chen, Qinjun; Zhou, Wenxi; Guo, Qin; Lu, Yifei; Li, Chao; Zhang, Yu; Liang, Donghui; Sun, Tao; Wei, Xunbin; et al.
Abstract: The frequent relapse and metastasis characteristics of triple negative breast cancer (TNBC) make it a fraught issue with very poor prognosis in clinic. An effective treatment for TNBC should prevent and even eliminate metastasis as well as suppress primary lesion expansion. Recent progress reveals that platelets can be recruited and activated by tumor cells through intercellular adhesion molecules (ICAM), and help aggressive circulating tumor cells (CTCs) form metastasis. Therefore, activated platelets are considered with possession of tumor‐homing, CTC‐capturing, and metastasis‐targeting abilities. In this work, a P‐selectin (expressed on activated platelet surface) targeting peptide (PSN) is modified on a redox‐responsive paclitaxel‐loaded micelle (PSN‐PEG‐SS‐PTX4 micelle) to utilize activated platelets as a "bridge" for interaction with cancer cells. The PSN‐modified micelle can easily adhere to the surface of activated platelets and subsequently capture CTCs in blood circulation. Compared to Taxol and PEG‐SS‐PTX4 micelle, PSN‐PEG‐SS‐PTX4 micelle also exhibits enhanced primary TNBC/metastasis targeting and penetrating effect through binding with tumor infiltrating platelets and thus significantly improves treatment outcome. More importantly, PSN‐PEG‐SS‐PTX4 micelle potently suppressed lung metastasis of TNBC and reduced incidence of distant liver metastasis. The activated platelet‐targeting redox‐responsive micelle system provides a promising prospect for the omnidirectional treatment of metastatic cancer. Abstract : A novel P‐selectin targeting micelle with controlled drug release is designed to utilize activated platelets as an endogenous device for efficient drug delivery to metastatic tumors. The micelle captures and eliminates circulating tumor cells via binding with activated platelets to prevent metastasis as well as penetrates and accumulates at primary tumors or metastasis via tumor‐infiltrating activated platelets.